Studi Analisis Kesiapan Desa Jelantik Kecamatan Jonggat Kabupaten Lombok Tengah menjadi Desa Wisata - Muhamad Alam Setiawan; Muharis Muharis (STIE Pariwisata API Yogyakarta, 2024)
The trend of traveling to rural areas emerged after the Covid-19 pandemic because tourists wanted tourism with a healthier nuance. Tourism Villages then massively come up to meet this tourism demand. Jelantik Village, located in Central Lombok Regency, West Nusa Tenggara Province, is one of the villages that is seen as highly potential village to develop into a tourist village due to its attractions. This study aims to determine the readiness of Jelantik Village to become a tourist village. The method used in this study is a qualitative descriptive method. There are three important elements that are the subject of study to see the readiness of Jelantik Village to become a tourist village, namely the readiness of the A3 elements (Attractions, Accessibility, and Amenities), community elements, and government elements. The result of the study shows that Jelantik Village can be considered to be the strong embryo of tourist village. The readiness of the A3 elements has almost been fully met. The elements of society and government are basically ready in their respective contexts. However, the lack of communication seems to be an obstacle to a proper collaboration between the two elements, the society and the government. There is a fact that the community and the government are waiting for each other in starting the collaboration process makes progress stagnant in efforts to develop tourist villages in Jelantik Village.